Erythrocyte sedimentation rate measured using microhemagglutination is not elevated in monoclonal gammopathy compared with other diseases. (23rd May 2018) - Kim, M.; Ju, Y.‐S.; Lee, E. J.; Lee, E.; Jeon, K.; Lee, J.; Kang, H. J.; Kim, H.‐S.; Lee, J.‐S.; Kim, H. J.; Lee, Y. K.
Abstract: Background: The erythrocyte sedimentation rate (ESR) as measured using the Westergren method is extremely elevated in patients with monoclonal gammopathy (MG) owing to the abundance of positively charged paraproteins. However, it has not been determined if the ESR is likewise high in patients with MG when measured using alternate ESR methods. Methods: The ESR was measured using both the modified Westergren and microhemagglutination method (TEST1) in 36 patients with MG and in 159 individuals with other diseases. Results: Erythrocyte sedimentation rates measured by the Westergren vs microhemagglutination methods showed substantial, but not remarkably high correlation. ESR measured using the Westergren method was higher in MG than in non‐MG patients; however, ESR measured using microhemagglutination was not different in the 2 groups, resulting in a larger ΔESR (microhemagglutination ESR—Westergren ESR) in MG patients. When considered as continuous variables, none of the tested interfering plasma proteins (C‐reactive protein, globulin, or fibrinogen) showed substantial correlations with Westergren or microhemagglutination ESRs. MG and low hematocrit were the only factors independently associated with ΔESR on multivariate analysis. Conclusion: We demonstrated, for the first time, that the ESR as measured by microhemagglutination is not elevated in patients with MG compared with those without. The ESR does not correlate with a particular plasma protein, showing that its measurement is multifactorial. The presence of MG is an independent factor for ΔESR.